Analysis of the Accountability of Land Deed Officials for the Transfer of State Land (Court Decision Number 33/Pdt.G/2019/Pn.Cbi) - Firmansyah Iswara, Alfido; Fajar Riyanto, Taufan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Protection of land based on the 1945 Constitution of the Republic of Indonesia (UUD 1945) can be found in several articles that emphasize the principle of state control over natural resources including land, as well as the state's obligation to regulate, manage and protect it for the prosperity of the people.The aim of this research is Uto find out and analyze PPAT's responsibilities in making deeds of transfer of state land and completing the transfer of rights to state land. The type of research used by the researcher is legal sociology. Legal sociology is a type of legal research known as field research, which relates to legal provisions and the realities of society.Descriptive-qualitative research. Descriptive-qualitative research is research that explains, records, analyzes, and interprets the object being studied based on observations, interviews, and documentation. The analysisThe qualitative method used is a way of interpreting and discussing research results based on interviews with informants, understanding of law, legal norms, legal theories and doctrines related to the main problem. The research results obtained were:The case of the transfer of Building Use Rights (HGB) involving PPAT in the case of PT Sentul City Tbk illustrates a form of negligence in the implementation of administrative authority and legal responsibility of PPAT as regulated in PP No. 24 of 1997 concerning Land Registration and Regulations on the Position of PPAT (Regulation of the Head of BPN No. 1 of 2006 in conjunction with No. 8 of 2012). The PPAT is considered to have violated the due care principle because it made a deed of transfer of land rights without ensuring the validity of the land status which is still legally problematic or overlaps with the rights of other parties. The case of the transfer of Building Use Rights (HGB) involving the PPAT in the case of PT Sentul City Tbk shows that the implementation of the PPAT's duties has a crucial role in realizing legal certainty in the land sector, resulting in the registration process and issuance of new certificates at the National Land Agency (BPN) being administratively flawed and creating legal uncertainty for the interested parties.